2021
DOI: 10.1177/0194599821995485
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Unilateral Hearing Loss and Impact on Communication in US Adults

Abstract: Objective To investigate the factors associated with unilateral hearing loss (UHL) and its impact on communication in US adults. Study Design Cross-sectional study. Setting Nationally representative sample of US adults. Methods We analyzed data from the 2011-2012 and 2015-2016 National Health and Nutritional Examination Survey, in which participants aged 20 to 69 years completed an audiometric evaluation (n = 8138). UHL was defined as a speech frequency pure-tone average ≥25 dB in the worse hearing ear and <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…30,31 This study found participants with higher education levels had lower odds of HL, which is consistent with prior literature. 13,27 The groups without a high school diploma had close to double the odds of HL as the college graduate or above group. When stratifying by HL severity in multivariate analysis, groups without a high school diploma were associated with moderate and severe/profound HL, but not with mild HL.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…30,31 This study found participants with higher education levels had lower odds of HL, which is consistent with prior literature. 13,27 The groups without a high school diploma had close to double the odds of HL as the college graduate or above group. When stratifying by HL severity in multivariate analysis, groups without a high school diploma were associated with moderate and severe/profound HL, but not with mild HL.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence on smoking as a risk factor for HL is mixed, but primarily favors findings that smoking is associated with increased risk of HL. 12,13,[33][34][35][36] A study of NHANES data from 2011-2012 and 2015-2016 found that smoking tobacco is associated with increased odds of HL. 33 The Nurses' Health Study II also showed an increased risk of HL in smokers, with increased risk with increased packyears and with shorter time since smoking cessation for former smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARHL is an extremely common disorder, and it has a spectrum of effects that ranges from an almost undetectable degree of disability to a profound alteration in the ability to function in society (Ciorba et al, 2012;Choi et al, 2021;Dalton et al, 2003;Ellis et al, 2021). It is a known fact that the onset of ARHL is often insidious, and is frequently accompanied by subtle compensatory strategies, hence is often overlooked by physicians and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss is independently associated with an increased risk of cognitive decline over time with significant associations between greater hearing loss and poorer cognitive function (Choi et al, 2021;Ellis et al, 2021;Lin et al, 2013). Social isolation and loneliness, may be the possible factors mediating the link between hearing loss and cognitive decline (Choi et al, 2021;Dalton et al, 2003;Ellis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%